Analysis of Prevalence of Oral Squamous Cell Carcinoma in Patients with History of Chronic Irritation of Oral Tissues - A Retrospective Study - Suvarna K1 , Abilasha.R2 , Gheena.S3 , Pratibha Ramani4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral squamous cell carcinoma (OSCC) accounts for more than 90% of the reported oral cancer cases inthe world. Even though the habits such as tobacco usage, smoking and old age are the main risk factors fordeveloping oral squamous cell carcinoma some factors like chronic mucosal irritation(CMI) from mechanicaland functional factors also play a significant role in the etiology of oral squamous cell carcinoma. The aimof this study was to analyse the prevalence of oral squamous cell carcinoma with history of chronic mucosalirritation and to evaluate various parameters like gender, age, site of the lesion and etiology of chronictrauma in OSCC cases with chronic mucosal irritation history. This retrospective study included a samplesize of n= 78 ( 73 = OSCC with other etiology, 5= OSCC with etiology of chronic mucosal irritation). Dataregarding the sample cases were selected after the review and analysis of records of about 86000 patientswho visited our institution between june 2019 and march 2020. The retrieved data were tabulated in MSExcel and exported to SPSS for statistical analysis. Prevalence of oral squamous cell carcinoma cases withchronic mucosal irritation history was 6.41% for a duration of 8 months. Etiology associated with chronicmucosal irritation was found to be tooth related factors in all the sample cases. 80% of the oral squamous cellcarcinoma cases associated with chronic mucosal irritation history were males and 20% were females and80% of the OSCC samples with CMI were above 40 years of age. In 60% of OSCC with CMI history werefound to be on buccal mucosa followed by tongue and gingivobuccal sulcus. The present study providesan overview and explains the need of considering chronic mucosal irritation as an etiological factor for thedevelopment of OSCC without the association of tobacco habit.